I couldn't think of an easy way to do this. So I wrote up a really complicated way to do it. Namely:
- Take the multidimensional array and flatten it into a list of keys and values.
- Reverse the keys.
- Unflatten the list to obtain an inverted multidimensional array.
Code
<?php
function print_entries($array, $prekeys = array())
{
foreach ($array as $key => $value)
{
$keys = array_merge($prekeys, array($key));
if (is_array($value))
print_entries($value, $keys);
else
echo '[' . implode('][', $keys) . "] = $value\n";
}
}
function flatten_array($array)
{
$entries = array();
foreach ($array as $key => $value)
{
if (is_array($value))
{
foreach (flatten_array($value) as $subentry)
{
$subkeys = $subentry[0];
$subvalue = $subentry[1];
$entries[] = array(array_merge(array($key), $subkeys), $subvalue);
}
}
else
$entries[] = array(array($key), $value);
}
return $entries;
}
function unflatten_array($entries)
{
$array = array();
foreach ($entries as $entry)
{
$keys = $entry[0];
$value = $entry[1];
$subarray = &$array;
foreach ($keys as $i => $key)
{
if ($i < count($keys) - 1)
{
if (!isset($subarray[$key]))
$subarray[$key] = array();
$subarray = &$subarray[$key];
}
else
$subarray[$key] = $value;
}
}
return $array;
}
function invert_array($array)
{
$entries = flatten_array($array);
foreach ($entries as &$entry)
$entry[0] = array_reverse($entry[0]);
return unflatten_array($entries);
}
$array = array
(
0 => array
(
5 => array('var_name' => 'data'),
3 => array('var_name2' => 'data2'),
1 => array(4 => array('var_name4' => 'data4'))
),
1 => array(0 => array('var_name' => 'data3'))
);
print_entries($array);
echo "\n";
print_entries(invert_array($array));
?>
Output
[0][5][var_name] = data
[0][3][var_name2] = data2
[0][1][4][var_name4] = data4
[1][0][var_name] = data3
[var_name][5][0] = data
[var_name2][3][0] = data2
[var_name4][4][1][0] = data4
[var_name][0][1] = data3
Edit: I noticed now that you don't reverse the keys but you simply move the var_name
portion from the end to the front and leave the numerical indices alone. It's easy enough to modify the line in flatten_array
where I call array_reverse
to re-order the keys in a different way. The core flatten/unflatten logic would not need to be changed. I leave this as an exercise for the reader. :-)